2005
DOI: 10.1677/joe.1.06179
|View full text |Cite
|
Sign up to set email alerts
|

The cytoplasmic domain close to the transmembrane region of the glucagon-like peptide-1 receptor contains sequence elements that regulate agonist-dependent internalisation

Abstract: In order to gain better insight into the molecular events involved in the signal transduction generated through glucagon-like peptide-1 (GLP-1) receptors, we tested the effect of deletions and point mutations within the cytoplasmic tail of this receptor with a view to establishing relationships between signal transduction desensitisation and receptor internalisation. Wild-type and truncated (deletion of the last 27 amino acids (GLPR 435R) and deletion of 44 amino acids (GLPR 418R)) GLP-1 receptors bound the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Widmann and colleagues did not observe internalization of a mutant receptor lacking the last 33 amino acids (Widmann et al, 1997) while Vazquez (Vazquez et al, 2005a) showed a 78% slower internalization of a modified receptor lacking the last 27 amino acids when transfected into fibroblast cell lines. In contrast when the 44 C-terminal amino acids were deleted (GLPR 418R), receptor internalization was only 47% slower with the mutant versus the wild-type GLP-1R, indicating an inhibitory role of the region containing amino acids 419-435 (Vazquez et al, 2005a). Specifically, when the three amino acids located proximal to TM 7 ( 408 EVQ 410 ) were replaced with alanine, internalization was found to be much faster.…”
Section: Glp-1r In the Pancreasmentioning
confidence: 98%
See 3 more Smart Citations
“…Widmann and colleagues did not observe internalization of a mutant receptor lacking the last 33 amino acids (Widmann et al, 1997) while Vazquez (Vazquez et al, 2005a) showed a 78% slower internalization of a modified receptor lacking the last 27 amino acids when transfected into fibroblast cell lines. In contrast when the 44 C-terminal amino acids were deleted (GLPR 418R), receptor internalization was only 47% slower with the mutant versus the wild-type GLP-1R, indicating an inhibitory role of the region containing amino acids 419-435 (Vazquez et al, 2005a). Specifically, when the three amino acids located proximal to TM 7 ( 408 EVQ 410 ) were replaced with alanine, internalization was found to be much faster.…”
Section: Glp-1r In the Pancreasmentioning
confidence: 98%
“…They have shown that GLP-1R is endocytosed via a primarily clathrin coated pitdependent mechanism and that in the presence of agonist the receptor cycles between the plasma membrane and endosomal compartments. The recognition sequence for the clathrin coated pit is located in the cytoplasmic tail of the receptor and C-terminally truncated mutants exhibit aberrant internalization rates (Vazquez et al, 2005a;Widmann et al, 1997). Widmann and colleagues did not observe internalization of a mutant receptor lacking the last 33 amino acids (Widmann et al, 1997) while Vazquez (Vazquez et al, 2005a) showed a 78% slower internalization of a modified receptor lacking the last 27 amino acids when transfected into fibroblast cell lines.…”
Section: Glp-1r In the Pancreasmentioning
confidence: 99%
See 2 more Smart Citations
“…The complete coding region for C57BL/6J and CAST/Ei Glp1r was subcloned into an expression plasmid pcDNA 3.1 (Invitrogen) and transfected into CHO-K1 cells (ATCC CCL-61; Ref. 56), graciously provided by Dr. Tom Gettys, using lipofectin (Invitrogen). Stable transfectants were obtained after selection for zeocin (zeo) resistance at a concentration of 0.5 mg/ml (Invitrogen) in DMEM containing 10% fetal bovine serum.…”
Section: For Diet Composition)mentioning
confidence: 99%